Breath Hydrogen Gas Concentration Linked to Intestinal Gas Distribution and Malabsorption in Patients with Small-bowel Pseudo-obstruction - Urita, Yoshihisa (Libertas Academica, 2009)
BACKGROUND: The patient with colonic obstruction may frequently have bacterial overgrowth and increased breath hydrogen (H2) levels because the bacterium can contact with food residues for longer time. We experienced two cases with intestinal obstruction whose breath H2 concentrations were measured continuously. CASE 1: A 70-year-old woman with small bowel obstruction was treated with a gastric tube. When small bowel gas decreased and colonic gas was demonstrated on the plain abdominal radiograph, the breath H2 concentration increased to 6 ppm and reduced again shortly. CASE 2: A 41-year-old man with functional small bowel obstruction after surgical treatment was treated with intravenous administration of erythromycin. Although the plain abdominal radiograph demonstrated a decrease of small-bowel gas, the breath H2 gas kept the low level. After a clear-liquid meal was supplied, fasting breath H2 concentration increased rapidly to 22 ppm and gradually decreased to 9 ppm despite the fact that the intestinal gas was unchanged on X-ray. A rapid increase of breath H2 concentration may reflect the movement of small bowel contents to the colon in patients with small-bowel pseudo-obstruction or malabsorption following diet progression. CONCLUSIONS: Change in breath H2 concentration had a close association with distribution and movement of intestinal gas.